A large-stroke compliant joint–based force/displacement integrated sensor. (17th December 2015) - Duan, Xuechao; Ge, Shibin; Fang, Hongmei; Bao, Hong
The design methodology and validation of a compliant translational joint–based force/displacement integrated sensor is presented in this article. The stiffness analysis of the large displacement high precision compliant translational joint is developed, in which the screw theory–based symbolic formulation method for structures is employed. By combining the stiffness matrix of the single compliant beams and components in this joint, the entire stiffness matrix is derived. The stiffness matrix is validated by finite element analysis (FEA) method. Finally, the compliant translational joint was fabricated with a three-dimensional printer and equipped with a linear position sensor and microcontroller. The displacement of the translational joint is measured and then the force is calculated using the stiffness matrix. A calibration is conducted so that the sub-Newton precision of the sensor is achieved.